Mengembangkan Pemikiran Falsafah Pendidikan Islam - Fahruddin, Mukhlis (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Dichotomic paradigm in Islamic education has brought about some difficulties in responding challenges of change. This dichotomic prototype even caused the backthrough of Islamic civilization. In spite of this, new paradigm of Islamic scientific epistemology which develop integratic andinterconected Islamic educational progress in the future is needed. The progress thoughts is needed in Islamic education to minimize disparity between science and religion.keywords: Epistemology, Philosophy, Development and Islamiceducation